TANGGUNG JAWAB PEJABAT PEMBUAT AKTA TANAH SEMENTARA (PPATS) AKIBAT KELALAIAN DALAM PEMBUATAN AKTA JUAL BELI TANAH ATAS PERALIHAN HAK ATAS TANAH. - Samosir, Ade Agnesia; Marniati, Felicitas Sri; Kumala, Yudha Cahya (SENTRI: Jurnal Riset Ilmiah, 2024)
An agreement concluded by agreement between the policyholder and the insurance company as an insurer and providing benefits to third parties, is valid as law. However, the provision of disbursement of insurance claim funds can only be made if the insured dies. So there is often a misunderstanding among family members who think that life insurance claims funds are considered an inheritance and must automatically be handed over to their heirs. Beneficiaries in life insurance do not refer to heirs but to those whose names are listed in the life insurance agreement. How is the legal provision of the rights of beneficiaries of life insurance on the claim of heirs ab intestato in Civil Law and how is the legal certainty of the life insurance agreement that regulates the beneficiaries in the life insurance policy? The theory used in this study is the theory of legal certainty from Jan Michael Otto and Mulhadi insurance theory The method used in this study is the normative juridical method, namely legal research conducted by researching library materials or secondary data only. The research approach used is the approach of legislation, case approach, analytical approach and conceptual approach. The technique of collecting legal materials is carried out by identifying and inventorying positive legal rules, researching library materials (books, scientific journals, research reports) and other sources of legal materials that are relevant to the legal issues under study. For technical analysis of legal material is done by systematic and grammatical interpretation. Based on the results of research conducted by the author, the life insurance agreement is not based on the provisions of inheritance law, so that the disbursement of insurance claim funds is given to beneficiaries as the contents of the agreement in the policy.